Injectable carbon nanotube-functionalized hydrogel as a tool for cardiac tissue engineering. (3rd October 2022) - Pena, B; Knight, W; Cavasin, M; Ferrari, I; Abdel-Hafiz, M; Vagnozzi, R; Bosi, S; Park, D; Shandas, R; Song, K; McKinsey, T; Sbaizero, O; et al.
Abstract: Background/Introduction: Heart failure (HF) is an expensive major public health problem in the United States and around the world (1). The current treatments for HF are aimed at reducing symptoms, slowing disease progression, and reducing mortality and not aimed at repairing heart muscle or restoring function. Furthermore, even with these treatments, approximately half of patients with HF will die within 5 years of diagnosis (2). Cardiac transplantation remains the only definitive treatment for those affected with end-stage HF, but availability of donor hearts remains a major limitation (3). Purpose: The ability of the adult heart to regenerate cardiomyocytes (CMs) lost after injury is limited, generating interest in developing tissue engineering therapies to avoid progression towards HF. Rigid carbon nanotubes (CNTs) scaffolds have been used to improve CMs viability, proliferation, and maturation (4), but require undesirable invasive surgeries for implantation. To overcome this limitation, we engineered an injectable reverse thermal gel (RTG) functionalized with CNTs (RTG-CNT) that transitions from a liquid-solution to a gel-based matrix shortly after reaching body temperature allowing for a liquid-based delivery rapidly followed by a stable-gel localization (5). Methods and results: Here we show experimental evidences the RTG-CNT hydrogel, used as a three-dimensional (3D) niche to culture human induced pluripotent stem cells (hiPSC)-CMs, promotes hiPSC-CMs alignment and elongation with increased Cx43 localization and improved contraction function when compared with traditional two-dimensional (2D) fibronectin controls and plain 3D RTG system without CNTs. Moreover, the short-term (4-week) biocompatibility of the RTG-CNT hydrogel was also assessed in a mouse model (intracardial injection). The results confirmed that the RTG-CNT hydrogel is well tolerated by the cardiac tissue. Conclusion: Our results indicated that the injectable RTG-CNT hydrogel has the potential to be used as a minimally invasive tool for cardiac tissue engineering efforts. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): NATIONAL HEART, LUNG, AND BLOOD (NHLBI) INSTITUTE